Assessing the interaction of price optimisation and system-wide transportation selection on a third-party logistics provider. (25th May 2011) - Lee, Yong Joo; Baker, Tim
We utilise a non-linear integer programming model of ABC's (the name of the company has been disguised) combined forward-reverse logistics system that enables them to enhance their strategic planning in three ways: We compare the recommendations from this model against the most representative (i.e., baseline) model for ABC's system in the extant literature. This baseline model does not perform 1–3. We show that considering 1–2 simultaneously results in significantly higher system-wide profits than just 1 alone, and that this profit increase is enhanced when ABC is operating in higher price elasticity markets. These results have promise to generalise to other third party logistics providers since their systems are similar.